Professional Project in a Neoliberal Environment and Evolution of the Meanings of Social Work: a Case Study in Italian Probation Field - Ruggero Capra (Social Work and Society)
In my PhD thesis proposal I want to contribute to the empirical clarification of the meaning of social work. This goal is rather wide and generic: therefore I have selected a theme and an event that I think could be useful for my aims. In the first paragraphs, I am going to explain the choices useful for building the research design. In the following ones, I am going to present some aspects of the field of research and my motivations, the theoretical frameworks, and the features of this case study. In the last paragraphs, I am going to deal with some initial results of my research. In particular, I am going to present the results of a documentary analysis that will allow me to better focus the core theme of my research. This step will allow me to go on with my research through interviews with some stakeholders. Moreover, this paper considers some comments from the International Supervisory Board of Tissa 2010.